Fairness and the support of redistributive environmental policies - Mark Andreas Andor; Andreas Lange; Stephan Sommer (RWI - Leibniz-Institut für Wirtschaftsforschung, 2022)
Exemptions from costly policy measures are frequently applied to alleviate financial burdens to specific market participants. Using a stated-choice experiment with around 6,000 German household heads, we test how exemptions for low-income households and energy-intensive companies influence the political acceptability of additional cost for the promotion of renewable energies. We find that the support for the policy is substantially higher when low-income households are exempt rather than the industry. Introducing exemptions for low-income households on top of existing exemptions for the industry increases the acceptability of the policy. We show that the support for exemptions as one example of distributional policy design is associated with individual behavioral measures like inequality aversion and fairness perceptions. – – Ausnahmeregelungen von politischen Maßnahmen, die hohe Kosten verursachen, werden häufig angewandt, um die finanziellen Belastungen bestimmter Marktteilnehmer zu mindern. Anhand eines stated-choice-Experiments mit rund 6.000 deutschen Haushaltsvorständen untersuchen wir, wie Ausnahmeregelungen für einkommensschwache Haushalte und energieintensive Unternehmen die politische Akzeptanz zusätzlicher Kosten für die Förderung erneuerbarer Energien beeinflussen. Wir stellen fest, dass die Unterstützung für die Politik wesentlich höher ist, wenn anstatt der Industrie einkommensschwache Haushalte befreit werden. Die Einführung von Ausnahmen für einkommensschwache Haushalte zusätzlich zu den bestehenden Ausnahmen für die Industrie erhöht die Akzeptanz der Politik. Wir zeigen des Weiteren, dass die Unterstützung für Ausnahmeregelungen - als ein Beispiel für die Ausgestaltung von Politiken mit Verteilungswirkung - mit individuellen Verhaltensmaßen wie Ungleichheitsaversion und Fairnesswahrnehmung zusammenhängt.
Keywords: D03; D12; H41; Q20; 330; Fairness; distributional effects; environmental policy; exemptions renewable energy; political acceptance; behavioral economics; discrete choice experiment